Kebijakan Affirmative Action 30% Keterwakilan Perempuan dalam Keanggotaan KPU Provinsi Lampung Perspektif Siyasah Tanfidziyah - Rifki Galuh Pratama; Efa Rodiah Nur; Li’izza Diana Manzil (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This research examines how the affirmative action policy targeting 30% women’s representation is applied in the composition of the Lampung Provincial General Election Commission (KPU) for 2024-2029, viewed through Siyasah Tanfidziyah. Affirmative action serves as a legal mechanism to promote representative justice and gender equality within political bodies. In practice, however, the final composition of the KPU in this period contains no female members, reflecting a gap between normative regulation and its realization. The study employs a qualitative, descriptive-analytical field approach. Data were obtained through interviews, document analysis, and literature review, then interpreted inductively. The results indicate that implementation of the policy remains suboptimal. Although female candidates reached the final selection stages, none were ultimately appointed. This outcome is influenced by several factors, including limited capacity among female candidates, regulatory provisions that lack binding force, and selection processes that are not fully gender-responsive. From the perspective of Siyasah Tanfidziyah, this situation demonstrates that the principles of justice (al-‘adl), accountability, and public benefit (maslahah ‘ammah) have not been fully achieved. Strengthening binding regulations, reforming selection mechanisms, and enhancing women’s capacity are essential to ensure more effective and sustainable implementation of affirmative action